Non Medical Interventions for Childhood Diarrhoea Control:Way Forward in Nepal - Khanal, V; Bhandari, R; Karkee, R (Kathmandu University Medical Journal, 2015)
Background Diarrhoeal diseases remain a major cause of mortality of children aged under-five years in the developing countries including Nepal. The transmission of diarrhoea mostly caused by biological agents and is facilitated by the behavioural, social and environmental factors. More recently, the concept of prevention altering these factors is getting momentum. Objective To recommend the most effective non medical intervention that can prevent and control childhood diarrhoeal disease in Nepal. Methods Litrature review was conducted to analyse the successful interventions in developing countries. Peer review articles were accessed from “Science direct”, “Google Scholar”, and “Pubmed”. Interventions focussing on social and environmental determinants of diarrhoea were included. Results Four interventions (with primary focus in social and environmental determinants of diarrhoeal disease) were purposively selected, summarized and discussed. Saniya programme (Burkina Faso 1995 to 1998) is considered successful in modifying the risk behaviours. Intensive hand washing programme (Pakistan 2002 to 2003), a cluster randomized controlled trail, was not sustainable as the results did not last long once the free supply of soap was stopped. School Led Total Sanitation (Nepal 2006) is a participatory, community centred program whose focus is on local ownership. This program approach is effective and feasible for scaling up in Nepal. Global Public Private Partnership for Hand washing with Soap (Ghana 2002) was based on the marketing researches and hence yielded effective results. Conclusion Combination of School Led Total Sanitation and Global Public Private Partnership for hand washing with soap suits Nepal. These interventions focus on creating demand, changing behaviour and thereby, improving the sanitation status. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12517 Kathmandu Univ Med J 2013; 43(3):256-261